Current computational trends in polyanionic cathode materials for Li and Na batteries. (22nd June 2018) - Chakraborty, Sudip; Banerjee, Amitava; Watcharatharapong, Teeraphat; Araujo, Rafael B; Ahuja, Rajeev
Abstract: A long-standing effort has been devoted for the development of high energy density cathodes both for Li- and Na-ion batteries (LIBs and SIBs). The scientific communities in battery research primarily divide the Li- and Na-ion cathode materials into two categories: layered oxides and polyanionic compounds. Researchers are trying to improve the energy density of such materials through materials screening by mixing the transition metals or changing the concentration of Li or Na in the polyanionic compounds. Due to the fact that there is more stability in the polyanionic frameworks, batteries based on these materials mostly provide a prolonged cycling life as compared to the layered oxide materials. Nevertheless, the bottleneck for such compounds is the weight penalty from polyanionic groups that results into the lower capacity. The anion engineering could be considered as an essential way out to design such polyanionic compounds to resolve this issue and to fetch improved cathode performance. In this topical review we present a systematic overview of the polyanionic cathode materials used for LIBs and SIBs. We will also present the computational methodologies that have become significantly relevant for battery research. We will make an attempt to provide the theoretical insight with a current development in sulfate (SO4 ), silicate (SiO4 ) and phosphate (PO4 ) based cathode materials for LIBs and SIBs. We will end this topical review with the future outlook, that will consist of the next generation organic electrode materials, mainly based on conjugated carbonyl compounds.